2012
DOI: 10.1007/s10008-012-1756-x
|View full text |Cite
|
Sign up to set email alerts
|

Grain boundary corrosion of the surface of annealed thin layers of gold by OH· radicals

Abstract: Annealed thin layers of gold with large monocrystalline areas were treated with OH · radicals generated in an electrochemical Fenton reaction. The morphological changes observed with ex situ atomic force microscopy in non-contact mode and grazing incidence X-ray diffractometry show that the grain boundaries, and generally the non-{111} planes, are the loci of highest reactivity, i.e., the places where the gold dissolution is much faster than on the {111} planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The signal AAu*(2) can be attributed to the oxidation of active gold sites associated to coordinatively unsaturated surface atoms [27, [30], [31], [32], [33], [34], [35], [36]] whose proportion is enhanced in the second scan as a result of the successive oxidative dissolutionreductive deposition-oxidative dissolution processes occurring during the sequence of the applied voltammetric runs [8]. In turn, the enhancement of the Ag stripping from the first to the second scan can be interpreted as a consequence of the generalized desilvering of gold.…”
Section: Voltammetric Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…The signal AAu*(2) can be attributed to the oxidation of active gold sites associated to coordinatively unsaturated surface atoms [27, [30], [31], [32], [33], [34], [35], [36]] whose proportion is enhanced in the second scan as a result of the successive oxidative dissolutionreductive deposition-oxidative dissolution processes occurring during the sequence of the applied voltammetric runs [8]. In turn, the enhancement of the Ag stripping from the first to the second scan can be interpreted as a consequence of the generalized desilvering of gold.…”
Section: Voltammetric Patternmentioning
confidence: 99%
“…In this context, electrochemical dating of archaeological gold is of particular interest because its voltammetric behaviour is rather well known [ [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39]], and, due to its noble character, the aging of this metal is much less sensitive to the 'local' physico-chemical conditions and their possible fluctuations over the entire time span to be dated. However, the electrochemical response of archaeological gold artefacts can be sensitive to the composition of the base metal (silver content in particular) and the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%
“…In the opinion of the authors of [12,13], it is based on the interaction of hydroxyl radicals, which result from the chemical reaction between the components of Fenton's reagent and Au 0 atoms con tained in microscopic defects (asperities) on the gold substrate (see also [26]). However, it should be taken into account that the cited works dealt with the polish ing of gold electrodes under the conditions of a voltage applied to them.…”
Section: Treatment Of Gold Nanoparticles With Fenton's Reagentmentioning
confidence: 99%
“…Tentatively, this increase in the active sites can be associated to the environmental attack, in particular, of reactive oxygen species. In recent works, Scholz et al showed that the attack of OH•radicals generated by the Fenton reaction produced features similar to typical grain boundary corrosion[49][50][51], whereas annealing of gold at high temperatures (900 ºC) and mechanical treatments (ultrasonication) produced variations of crystallinity, modification in the grain size and formation of gold surfaces with preferred crystallographic orientations[52].…”
mentioning
confidence: 99%